As pesquisas que tratam sobre fluência nas tecnologias digitais em Educação Matemática no período de 2009 a 2021: a contribuição da PUC-SP - Ferreira, Suely de Fátima (2022)
This work presents a mapping of the research carried out at PUC-SP whose initiatives used digital technologies, considering the works that involved the most diverse central themes, whether related to learning, teaching or teacher training. The main theoretical references used include studies on fluency in digital devices, reflections on intelligence technologies and analyzes of possible integrations between people and technologies at school and in society. The survey in question refers to theses and dissertations and uses the CAPES Catalog of Theses and Dissertations. In the context of digital technologies, the theme of the present research, a mapping, focused on fluency and its influence on teaching or learning processes